A educação científica de Rui Barbosa e o manual didático primeiras lições de coisas de Norman Calkins - NAZARÉ, Edlani Santos Araújo (2023)
Different research in the area of science teaching highlights the importance of reflections on science beyond the usual discourses concerning scientific concepts. In order to overcome these difficulties, we can see the potential of including elements from the History of Science in the training process of science teachers. The objective of this study is to develop a historical analysis of the ideas of scientific education that circulated in Brazil, in the final decade of the Empire, which triggered discussions about the structuring of Science teaching, between the years 1879 and 1889. The study was guided by the questions: What were the main characteristics of Brazilian public education in the imperial period? How did the spread of current science teaching in other countries at the time influence the pedagogical proposals for science teaching in Brazilian primary schools? How did the scientific education advocated by Rui Barbosa impact science teaching? In an attempt to obtain answers, referring to the time frame under study, the context of circulation and implementation of pedagogical renewal proposals in primary schools at the time was investigated, seeking to identify possible pedagogical conceptions about science teaching and its association with the intuitive method. To answer these questions, a brief characterization of Brazilian public education during the empire was carried out, with theoretical and methodological contributions, identifying the scientific ideas that supported science teaching during the period covered by the study. A bibliographical review of academic productions that used, as an object of study, the didactic manual translated by Rui Barbosa, was prepared. The relevance of the manual Primeiras Lições de Pessoas – the translation by Rui Barbosa – was observed as an initial step towards scientific education in Brazil. The analyzes were developed within the scope of the History of Science. It was found that the process of modernization of the nation, from the perspective of industrial development, was the main aspect that triggered an intense cycle of debates about the renewal of Brazilian public education, in which the school began to assume a role totally different from that it played in previous years.